The Implementation of Problem Based Learning Integrated With Technology to Improve Writing Skills - I Gusti Ngurah Mahotama Mandala Kepakisan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Problem-based learning (PBM) has been proven effective in improving students' active learning and problem-solving skills. This article examines the application of technology-integrated PBM methods as an approach to improving students' writing skills. In this study, learning support software and teacher consultation were used in the development of problem scenarios related to curriculum content. Qualitative research provides detailed and relevant information. The researcher used qualitative research methods because qualitative research provides detailed information about the application of technology-based problem-based learning to improve writing skills. The library learning method consists of activities related to collecting bibliographic information, reading and recording, and managing written materials. Qualitative research uses secondary data obtained from literature reviews such as; References, journals, articles and sources related to the research. The information obtained was analyzed using interpretative analysis. This means that the information collected is interpreted or explained, and the analysis is not just a description, but also a precise explanation and interpretation. This method involves several steps, starting with problem identification, research, collaboration and solution development. This case study made extensive use of secondary education literature as a source of literary material. The results show that students' writing skills improved significantly after applying this approach. The practical implication of the findings is that combining PBM and technology can be an effective strategy to improve students' writing skills.